Penggunaan Aplikasi MARBAH (Mari Belajar Asmaul-Husna) Sebagai Media Pembelajaran PAI di Sekolah Dasar - Desti Selviani; Amelia Destyani Pratiwi; Fitria Nur Aeni; Ani Nur Aeni (Departement of Mathematics Education, 2023)
This research is based on the existence of problems that occur in the learning process in elementary schools from an Islamic perspective. One of the efforts to increase knowledge and understanding regarding Asmaul Husna is through the use of the MARBAH Application learning media (Let's Learn Asmaul Husna). Learning media products for the MARBAH application are designed according to the needs and characteristics of students in elementary schools. Making media products for the MARBAH application aims to assist teachers in teaching Asmaul Husna material and is expected to help improve the competence, motivation and achievement of students in elementary schools. The MARBAH Application learning media contains PAI material, namely Asmaul Husna which contains material, readings and their meanings, videos containing Asmaul Husna songs and quizzes related to Asmaul Husna material. The method used in this study is the Design and Development (D&D) method using the ADDIE development model. The trial of the MARBAH application product involved grade VI students and teachers as research subjects. The results of the validation test from the research subjects indicated that the learning media product of the MARBAH Application was feasible to be used in the learning process in elementary schools.